Export and Regional Growth: A CGE Approach - Fernando Perobelli; Eduardo Haddad (European Regional Science Association (ERSA), 2004)
The relationship between trade and growth has been a familiar topic of discussion in the development literature. More often, the question posed concerns the effects of international trade on economic growth, and thus focuses on trade as an active “agent” of growth. This active role played by international trade can be found in many different models. Todaro (1994) concludes that trade can be an important stimulus to rapid economic growth, although it might not be a desirable strategy for economic and social development. The contribution to development depends on the nature of the export sector, the distribution of its benefits, and the sector's linkages with the rest of the economy. It seems that, to the extent we are only interested in the effects of international trade on pure economic growth, there is a consensus that trade can provide an important stimulus to growth. At the sub-national level, the export base theory provides the foundations to different models of regional development. Recently, however, given the focus on globalization issues and the implicit assumption that a region's economic future is inextricably tied with its ability to compete in the international export market, international trade has attracted the attention of regional analysts as well. In this paper we address some of these issues. An interstate CGE model is implemented to simulate the likely implications of state export growth on the structure of the Brazilian economic interregional system. Key-words: regional development, computable general equilibrium, trade.
Keywords: 330